Endogenous Creditor Seniority and External Debt Values - Dooley, Michael; Stone, Mark. (Washington, D.C. : International Monetary Fund, 1992)
A new aggregation scheme used to measure the sources of fiscal financing of indebted countries suggests that there was a fundamental improvement in the seniority of domestic debt at the expense of foreign bank debt during the late 1980s. We argue that this was the revenue maximizing response of governments to internal and external capital flight that drained the domestic financial 'tax base' subject to indirect taxation. Empirical analysis indicates that the profile of the sources of fiscal financing influenced external debt values. The econometric analysis also implies that previous studies have neglected an important reason for the decline in loan values from 1985 to 1989: the increase in international interest rates.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet